MEMBANGUN AKSES BAHASA ARAB DI MASYARAKAT: LIVING ARABIC RAMAH MASJID SEBAGAI BENTUK PENGABDIAN DI MASJID AL-HIDAYAH PAGAR DEWA - Akbar, Muhamad Randi; Maulana, Fandi; Martina, Lidian; Ananda, Quinnita Marli (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
This study explores the impact of a mosque-friendly Arabic language learning approach through songs and vocabulary at Masjid Al-Hidayah Pagar Dewa. The research aims to identify how integrating music and contextual vocabulary within the mosque environment enhances learners’ motivation, comprehension, and practical use of Arabic. Utilizing qualitative methods, including observations, interviews, and surveys with mosque attendees, the findings reveal that this innovative approach fosters a more engaging and supportive atmosphere for language acquisition. The study concludes that incorporating culturally relevant and enjoyable learning tools, such as songs and thematic vocabulary, effectively promotes active Arabic language use in religious settings, contributing to both linguistic proficiency and spiritual enrichment.